Autologous platelet-rich gel versus vitamin B12 for the treatment of grade III-IV acute radiation dermatitis in malignant tumor patients undergoing radiotherapy: an open-label randomized controlled clinical trial - Tao, Haiyun; Xiong, Chun; Tan, Lanju; Xie, Na; Chen, Jiaxin; Xie, Huadong; Le, Wenjun; Zhong, Hengcheng; Liang, Weiming; Shen, Yongqi (Frontiers in Oncology, 2025)
BackgroundAcute radiation-induced dermatitis (ARD) remains the most prevalent adverse event associated with radiotherapy;however, effective management options remain limited.This study was designed to evaluate the efficacy and safety of autologous platelet-rich gel(APRG) versus vitamin B12 in the treatment of grade III to IV acute radiation dermatitis in patients with malignant tumors.Materials and methods40 patients diagnosed with Grade III–IV acute ARD were randomly assigned in a 1:1 ratio to either the APRG group (n = 20) or the vitamin B12 group (n = 20). All patients received wound cleansing prior to intervention. In the APRG group, the prepared gel was sprayed onto the wound surface, which was then covered with sterile Vaseline gauze and a secondary dressing for 2 to 3 days. In the vitamin B12 group, wounds were treated with a wet compress consisting of 5 mg vitamin B12 dissolved in 100 mL normal saline, applied for 30 minutes per session, three times daily. ARD severity was graded according to the RTOG criteria, and adverse events (AEs) were assessed using CTCAE v4.0 by trained oncologists. The numerical rating scale (NRS) for the topical pain and Quality of Life Instrument for Cancer Patients in China (QOL-CCC) were subjectively reported by patients.ResultsThe APRG group demonstrated a significant shortening in the median healing time for ARD compared to the Vitamin B12 group (3.0 days, IQR: 2.0-4.0 vs. 8.0 days, IQR: 5.0-12.0; p < 0.001). Furthermore, patients treated with APRG reported consistently and significantly lower pain levels from day 2 through day 7 post-therapy (F = 24.288, P < 0.001). Superior improvements in five key quality-of-life domains—sleep, mental state, fatigue, activities of daily living, and appetite—were also observed in the APRG group (all P < 0.05). Critically, no treatment-related adverse events were recorded in the APRG group during the follow-up period.ConclusionOur findings establish APRG as a superior and transformative intervention over Vitamin B12, demonstrating significant efficacy in accelerating wound healing, reducing pain, improving patient quality of life, and maintaining a safe treatment profile.Registration Detailshttps://www.chictr.org.cn/showproj.html?proj=222262, identifier ChiCTR2400081656.